EVALUATION OF TARIFFS OF TRANSPORTING NATURAL GAS (TOLL FEES) ON PIPE SECTION X BY ANALYZING THE SENSITIVITY THE SENSITIVITY OF THE COST OF SERVICE PARAMETERS - Aulia Alfath; Bayu Satiyawira; Cahaya Rosyidan; Havidh Pramadika; Ratnayu Sitaresmi; Livia Ailen Dharma (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2020)
Indonesia has large enough gas reserves to meet household and industrial needs. It's just that, the price or the existing gas-related system is not maximal yet. One of the things that can ease the burden on the state is the use of household gas networks, some people are still hesitant to use it even though the price is relatively cheap compared to LPG. In determining the gas price, one of the components that has an effect on determining the gas price is the toll fee through pipes to be channeled. So the authors aim to conduct this research in order to educate and maximize solutions for energy dependency, for example the location I took is located in North Sumatra Province, with a pipeline stretching 156.5 km from X1 to X3. With OD 16 "along 18.5 km and existing OD 12" along 138 km. The maximum capacity of the two pipes is 150 MSCFD and 75 MSCFD, and the average volume that flows is not up to 10%. The construction of the pipe requires a cost of $ 42,391,716 USD, and nearly 55% of the total is pipe material including fittings, coatings, and others. With an average annual revenue of $ 11.561943 this project alone should have been able to return on investment for less than 5 years. With tariff analysis, the amount can be optimized with volume by reducing a few dollars per MSCF, to $ 7.49 making it more economical.